Hendiadys et construction de l’événement en anglais contemporain - Collin, Catherine (Neophilologica, 2014)
The present study investigates the construction of an event through the coordination of two predicates in English. Syntactic and semantic evidence indicates that the two verbs cannot be simply referred to as separate predicative units, but that they form a single conjoint, and this construction occurs in a variety of uses. Most of the literature on this construction deals with its formal properties and the comparison with the Try to V structure (Jespersen, 1940; Lind, 1983; Stefanowitsch, Gries, 2003; Hommerberg, Gunnel, 2007). Through the presentation and the discussion of the data, the present analysis shows that it is possible to offer a unified account of the different uses of the hendiadic structure, and clarifies the role, function and grammaticalisation of and in the coordinated structure. The use of the V and V structure is said to be mainly restricted to speech and almost absent in the press (Bib e r et al., 1999). Through the study of a journalistic corpus (The Independent (1992—2009) and The Guardian (1996—1999; 2006—2007)), which amounts to 759 million words, the paper discusses the precise nature of the mechanism of the V and V structure and sheds lights upon the schematic properties of the construction of an event.